Dietary fatty acids promote gut health in weaned piglets by regulating gut microbiota and immune function - Fan, Zongze; Lei, Lei; Wu, Xingyue; Xing, Ronghui; Du, Pengfei; Wang, Ziyang; Zhao, Huijuan; Huang, Yanqun; Chen, Wen; Si, Xuemeng (Frontiers in Microbiology, 2025)
BackgroundPost-weaning diarrhea in piglets is a common challenge that adversely impacts growth performance and increases mortality, leading to severe economic losses. Medium-chain fatty acids (MCFA) and short-chain fatty acids (SCFA) are frequently used as feed additives due to their bioactive properties. This study evaluated the effects of two different blends of MCFA and SCFA (VSM and VS + VM) as alternatives to zinc oxide (ZnO) on growth performance, nutrient digestibility, oxidative stress, inflammatory, and gut microbiota composition in weaned piglets.Methods and resultsA total of 108 piglets (8.22 ± 0.51 kg) were randomly assigned to three treatments: control (CON, basal diet + ZnO), VSM (basal diet + higher MCFA and lower SCFA content) and VS + VM (basal diet + higher SCFA and lower MCFA content). Results indicated that Both VSM and VS + VM, can replace ZnO to relieve diarrhea of weaned piglets as evidenced by increased average daily gain (ADG) and decreased feed to gain ratio (F/G) in 1–15 days, with no difference in final body weight compared to the CON group. Additionally, dietary MCFA and SCFA supplementation improves anti-oxidative and anti-inflammatory capacity by decreased of malondialdehyde (MDA) activity, and inhibited proinflammatory cytokine tumor necrosis factor α (TNF-α) and interleukin (IL-1β, IL-17A) secretion. Further study showed that the protective effect of MCFA and SCFA were associated with restoring gut barrier, upregulating abundances of Lactobacillus and Roseburia of piglets.InterpretationCollectively, the combination of MCFA and SCFA alleviated oxidative stress, modulated inflammation, and supported gut barrier function in weaned piglets, offering a promising alternative to ZnO, with VSM showing superior effects.